2015
DOI: 10.2147/ott.s95500
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of BRG1 inhibits proliferation and metastasis of lung cancer by regulating tumor suppressor miR-148b

Abstract: BackgroundBrahma-related gene 1 (BRG1) has been implicated in a variety of biological processes, and it has been found to be mutated or silenced in numerous cancers, including lung cancer. Recent reports have proposed BRG1 as a tumor suppressor, but its roles in cell proliferation and metastasis remain unknown. miR-148b functions as a tumor suppressor in non-small-cell lung cancer. However, the mechanism responsible for the downregulation of miR-148b in lung cancer is still elusive.MethodsThe expression of BRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…miR-152 represses the tumor growth of endometrial cancer [40]. miR-148b regulated by BRG1inhibits proliferation and metastasis lung cancer [47]. These studies suggested the critical role of miR-148/152 family on regulating tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-152 represses the tumor growth of endometrial cancer [40]. miR-148b regulated by BRG1inhibits proliferation and metastasis lung cancer [47]. These studies suggested the critical role of miR-148/152 family on regulating tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-148b-3p is dysregulated in numerous types of cancer ( 46 – 48 ). For example, in colorectal cancer, it is downregulated and acts as a tumor suppressor by targeting the CCKBR gene ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the roles of miR-148b in regulation of tumor repression have been widely studied, only a few studies suggested ROCK1 and BRG1 as molecular targets related to EMT regulation [125,126]. Nevertheless, two studies have suggested that miR-148b in exosomes derived from mesenchymal stem cells and fibroblasts suppress EMT in recipient tumor cells [127,128].…”
Section: Therapeutic Candidates For Preventing Exosomal Emt Inductionmentioning
confidence: 99%